Traffic Compliance Index of Acehnese Community - M Gaussyah; Dedy Yuliansyah (Kanun Jurnal Ilmu Hukum, 2021)
The purpose of this article is to analyze and discuss the correlation between the behavior of the Acehnese and the culture of traffic discipline. Every road user is obliged to obey the traffic rules, but the number of accidents is increasing every year, resulting in numerous deaths, injuries and property damage. This is an empirical legal research using a survey method with a qualitative approach. Interviews, observations, and file review is also used in this research. The results show that the traffic behavior of Acehnese remains poor, with the observation-based traffic compliance index having a value of 5.41 on a scale of 1-10. Most violations were committed by male drivers with 2 (two) wheels. The most common violations are not wearing a helmet, not turning on the main lights during the day, and not having a driver's license (SIM). Most traffic violations are committed by individuals between the ages of 17 and 40, most of whom have a high school education or equivalent. It is necessary to optimize the socialization of traffic discipline and the arrangement of traffic fiqh by the Aceh Provincial Police of Traffic Department (Ditlantas Polda Aceh), local authorities and related agencies.